CROSS-SECTIONAL STUDY ON ADVERSE PREGNANCY OUTCOMES AMONG FEMALE HEALTHCARE WORKERS IN KUCHING, SARAWAK - Gregory, Xavier; Anselm, Su Ting; Teh, Jo Hun (2020)
The weight of occupational risk on women in addition to men, is on their fecundity. NIOSH lists disorders of reproduction as one of the top ten leading work-related diseases and injuries. Nevertheless, women in the workforce is increasing and in healthcare, females make up the majority. This research is to observe the occurrences of adverse pregnancy outcomes among female healthcare workers in relation to their work schedules and its significance in relation to non-healthcare workers. Across-sectional study was carried out using a questionnaire with 469 respondents; 339 healthcare and 130 non-healthcare workers, reporting 564 pregnancies. In this study, adverse pregnancy outcomes among female healthcare workers is significantly higher than non-healthcare workers. There are no significant findings between healthcare and non-healthcare workers with respect to the types of adverse pregnancy outcomes and the work schedule. However, from the respondents' lifetime pregnancy outcome, we find that complete miscarriage occurred more frequently among healthcare workers who work on shift. Healthcare workers do experience a higher risk of adverse pregnancy outcomes, commonly occurring among those who work on shift/on-call.